91.4k views
1 vote
-3z-1=1-7z simplify​

User Gibbss
by
4.7k points

1 Answer

1 vote

Answer:

z = 1/2

Explanation:

Step 1: Write equation

-3z - 1 = 1 - 7z

Step 2: Solve for x

  1. Add 7z to both sides: 4z - 1 = 1
  2. Add 1 to both sides: 4z = 2
  3. Divide both sides 4: z = 1/2

Step 3: Check

Plug in z to verify it's a solution.

-3(1/2) - 1 = 1 - 7(1/2)

-3/2 - 1 = 1 - 7/2

-5/2 = -5/2

User Vania
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.